Le traitement médiatique des violences faites aux femmes : entre instrumentalisation et invisibilisation - Association Faire Face (Glad!)
Based on the experience and reflections of the feminist self-defense Association Faire Face, this article presents an analysis of the instrumentalization of violence against women by the media and by political discourses. Through media examples, we study how the important media coverage of violence in the public space contributes to invisibilize violence in private spaces and can lead to a restriction of women mobility. By perpetuating the myths that streets are more dangerous for women than private spaces, these rhetorics increase their sense of insecurity. Moreover, focusing on violence perpetrated by certain populations (racialized and / or from the popular class) invisibilizes violent acts perpetrated by men from other social groups as well as the specific violence experienced by racialized women in the public space. Finally, the process of appropriation of feminist practices is discussed, with the example of "women’s self-defense" initiatives. We reaffirm that feminist self-defense is a tool for empowerment, self-confidence, awareness of one’s own weapons by and for women.